Proceedings of the Graduate Research in Education Seminar (GREduc) 2019 - Faculty of Educational Studies (Faculty of Educational Studies, 2019)
The Graduate Research in Education Seminar (GREDuc) 2019, held on December 13, 2019, and organized by the Faculty of Educational Studies, Universiti Putra Malaysia, focused on the theme Humanising Education and Human Resource Development through Value Driven Research and Practices